Solving the Mysteries of the Solid Elements (from the Origin of Elements to Machine Parts) - Mae, Yoshiharu (Cambridge Scholars Publisher, 2019)
Most of the elements in the periodic table are metallic or semi-metallic elements. This book graphically represents these elements, allowing their nature to be interpreted in more detail. Each element is plotted in a diagram with thermal conductivity on the abscissa and the Young's modulus on the ordinate.
Keywords: Metals.; Métaux.; metal.; Metals; Libros electrónicos.